2011
DOI: 10.1590/s0102-09352011000300019
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable oil sources in diets for freshwater angelfish (Pterophyllum scalare, Cichlidae): growth and thermal tolerance

Abstract: The influence of fatty acid composition of the diets on the productive performance and on cold and heat tolerance of juvenile freshwater angelfish (Pterophyllum scalare), in three different phases, was studied. Phase I studied the productive performance of freshwater angelfish in a completely randomized experimental design with four treatments, canola, linseed, olive and soybean oils and four replicates during 50 days using 192 fish in 16 aquaria. Phase II studied the cold tolerance of juvenile freshwater ange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
3
3
0
Order By: Relevance
“…With respect to growth, the result of the present study corroborates with reports in the literature that lipid increase at an adequate level can improve fish growth, since requirements as to energy and, mainly, essential fatty acids, such as α-linolenic acid, are met (Ikeda et al, 2011). Flaxseed oil with a high dietary content increased α-linolenic acid (n-3) in the diet, positively impacting the growth of the zebrafish, possibly showing the animal's high capacity to digest and absorb this component.…”
Section: Discussionsupporting
confidence: 90%
“…With respect to growth, the result of the present study corroborates with reports in the literature that lipid increase at an adequate level can improve fish growth, since requirements as to energy and, mainly, essential fatty acids, such as α-linolenic acid, are met (Ikeda et al, 2011). Flaxseed oil with a high dietary content increased α-linolenic acid (n-3) in the diet, positively impacting the growth of the zebrafish, possibly showing the animal's high capacity to digest and absorb this component.…”
Section: Discussionsupporting
confidence: 90%
“…These results corroborate those of Sagne et al, (2013) who obtained the best FCR with diet E (equal proportion of peanut oil and soybean oil) with a FCR of 1.37 versus 1.77 for regime A (100% HP). However, they are similar to those of Kamarudin et al, (2011) who found FCRs ranging from 1.6 to 1.9 in his study on the effects of the replacement of food fish oil by different sources of food, Vegetable oil on the growth performance and tissue fatty acid profiles of Tor tambroides juveniles.…”
Section: Growth Performance Feed Efficiency and Survivalsupporting
confidence: 88%
“…These results are superior to those obtained by Ochang et al (2007) with results ranging from 0.62 to 0.85 in his study on the replacement of cod liver oil with palm oil in Clarias gariepinus. As well as those obtained by Ikeda et al, (2011) on Pterophyllum scalare anguillaris with SGR ranging from 0.44 to 0.50.…”
Section: Growth Performance Feed Efficiency and Survivalsupporting
confidence: 81%
“…The effect of dietary lipids on CT max and lethal thermal limits has also been assessed in a handful of studies, with mixed results. Oil type did not influence upper thermal limits in juvenile angelfish [56], but total lipid composition (10 versus 20%) had a significant effect on CT max in juvenile barramundi [31]. The effect of dietary fats on cardiac thermal plasticity in fish is relatively unknown.…”
Section: Discussionmentioning
confidence: 99%